A Practical Approach to Avoiding Iatrogenic Creutzfeldt-Jakob Disease (CJD) from Invasive Instruments. (8th April 2015) - Brown, Paul; Farrell, Michael
<x content-type="archive" xml:space="preserve">Abstract</x> Potential Creutzfeldt-Jakob disease instrument-contamination events continue to occur, causing widespread hospital and patient concern. We propose the use of a combination of diagnostic tests (ie, spinal fluid for 14-3-3 protein or nasal brushing for misfolded prion protein) and instrument handling procedures (ie, using a regional set of dedicated instruments), which if applied to all patients admitted with symptoms of either dementia or cerebellar disease, should eliminate the risk of iatrogenic instrument infection. Infect Control Hosp Epidemiol 2015;36(7):844–848